2011
DOI: 10.1016/j.jjcc.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mutations in the α-galactosidase A gene in patients with Fabry disease: Pitfalls of mutation analyses in patients with low α-galactosidase A activity

Abstract: We could identify GLA gene mutations in all hemizygotes and heterozygotes from 10 families with Fabry disease. Mutations in 4 out of 10 families could not be identified by classical genomic analysis, which focuses on exons and the flanking region. Instead, these data suggest that MLPA analysis and cDNA sequence should be considered in genetic testing surveys of patients with Fabry disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Family A It was difficult to diagnose FD due to large deletion of GLA in female subjects II-1, II-4, and II-5, as they did not show Some previous studies have shown the effectiveness of MLPA analysis to detect large deletions of the GLA gene in female FD patients (Marziliano et al 2012;Yoshimitsu et al 2011;Schirinzi et al 2008). We found deletion mutations with multiple exons from exon 2-5 elements using MLPA analysis in this family.…”
Section: Discussionmentioning
confidence: 73%
“…Family A It was difficult to diagnose FD due to large deletion of GLA in female subjects II-1, II-4, and II-5, as they did not show Some previous studies have shown the effectiveness of MLPA analysis to detect large deletions of the GLA gene in female FD patients (Marziliano et al 2012;Yoshimitsu et al 2011;Schirinzi et al 2008). We found deletion mutations with multiple exons from exon 2-5 elements using MLPA analysis in this family.…”
Section: Discussionmentioning
confidence: 73%
“…86,87 In females, due to the presence of the wild-type allele, gross GLA gene rearrangements, such as deletion or insertion of entire exons, may be missed, unless specific laboratory technique, such as multiplex ligation-dependent probe amplification analysis and/or quantitative polymerase chain reaction amplification, are used. 88,89 Additional investigations are also necessary in order to assess the pathogenicity of new variants. In silico and mRNA analysis, computational modeling, and functional studies are needed to prove or exclude the effect of the new identified variant as a disease-causing mutation.…”
Section: Biochemical Diagnosismentioning
confidence: 99%
“…Fabry disease is a lysosomal storage disorder (LSD) caused by deficient activity of the lysosomal hydrolase α-galactosidase A (α-gal A) (EC 3.2.1.22), encoded by the gene GLA [1,2]. The presence of dysfunctional α-gal A or its absence leads to progressive accumulation of neutral glycosphingolipids with α-D-galactosyl residues, mainly globotriaosylceramide (Gb3), in a variety of cell types, and results in multi-system disease [3].…”
Section: Introductionmentioning
confidence: 99%